The effect of four alternative chilling regimes on the bacterial load on beef carcasses. (May 2021) - McSharry, Siobhán; Koolman, Leonard; Whyte, Paul; Bolton, Declan
Abstract: The objective of this study was to compare the effect of current (10 °C for 10 h followed by 0 °C with a low fan speed) versus four alternative beef carcass chilling regimes, ranging from -6 °C to 0 °C and wind speeds between 1.5 and 6 m/s on the microbiology of beef carcasses. The temperature and relative humidity (RH) in the chillers, the carcass core and surface temperature, pH, water activity (aw ) and carcass weight (drip) loss were recorded. Bacterial concentrations (total viable counts (TVC), total Enterobacteriaceae counts (TEC), Pseudomonas spp., lactic acid bacteria (LAB) and Brochothrix thermosphacta ) were also monitored. Similar pH, aw and drip loss (2%) values were obtained regardless of chilling regime. For the most part, bacterial concentrations were also similar and, where statistically significant ( P < 0.05) counts occurred, the reductions were low (≤1 log10 cfu/cm 2 ). It was concluded that the current chilling regime was as effective as the tested alternatives in terms of the bacterial quality of the carcasses. Highlights: Current versus alternative beef carcass chilling regimes were evaluated. Similar bacterial concentrations and reductions (≤1 log10 cfu/cm 2 ) were observed. Chilling regime did not affect pH, water activity or drip loss.